Acupuncture for Dyspnea in Lung Cancer: Results of a Feasibility Trial. (17th February 2016) - Bauml, Joshua; Haas, Andrew; Simone, Charles B.; Li, Susan Q.; Cohen, Roger B.; Langer, Corey J.; Mao, Jun J.
Purpose. Dyspnea is a common and distressing symptom for patients with lung cancer (LC) because of disease burden, therapy toxicity, and comorbid illnesses. Acupuncture is a centuries-old therapy with biological plausibility for relief of dyspnea in this setting. This pilot study aimed to evaluate the feasibility and preliminary effectiveness of acupuncture for dyspnea among patients with LC. Methods. Eligible patients had a diagnosis of LC and clinically significant dyspnea without a clear organic cause. The treatment consisted of 10 weekly acupuncture sessions, with a follow-up visit 4 weeks after therapy. The primary outcome was dyspnea severity as measured using a validated Numerical Rating Scale (NRS) of 0 to 10 (10 being "most severe shortness of breath imaginable"). Results. We enrolled 12 patients in the study. The median age was 64.5 years; 66.7% of the patients were female, and 66.7% were Caucasians. Among those enrolled, 10 (83.3%) were able to complete all 10 acupuncture sessions. Acupuncture was well tolerated; adverse events were mild and self-limited. Mean (SD) dyspnea scores on the NRS improved from 6.3 (1.7) at baseline to 3.6 (1.9; P = .003) at the end of treatment and 3.2 (2.3; P = .008) at follow-up. Fatigue and quality of life also improved significantly with acupuncture ( P < .05). Conclusion. Among patients with LC, acupuncture was well tolerated and exhibited promising preliminary beneficial effects in the treatment of dyspnea, fatigue, and quality of life. Performing a trial in this population appears feasible.